Perspective of taxpayers toward religious donations and taxes from the viewpoint of religion - Yovita Widyadinata (Universitas Hayam Wuruk Perbanas, 2014)
This research aims to see the factors establishing the basis of Christian and Muslim taxpayers for being more obedient in paying their religious duties such as donations or zakat. The data were gathered through in-depth interview and analysis of the factors that become the basis for Christian and Muslim taxpayers to be more obedient in paying alms or tithes than in paying tax. The taxpayers interviewed for this study are religious leaders of Muslims, called Ustadz, and religious leaders of Christians, called Pastor. Besides, this research also uses documentation study method, in which the sources are taken from articles, and literature study method, in which the sources are taken from Bible, Qur’an, and Tax Regulations. The result of this research indicates that the biggest factor affecting Christian and Muslim taxpayers to be more obedient in paying alms or tithe than in paying taxes, as their obligation of the Indonesianpeople, is due to the allocation. The allocation of alms or tithe is considered more transparent than that of taxes.